Locating Community in disaster Management: A Comparative Study of Indonesia and India - Arindam Roy (Khazanah Sosial, 2022)
Unlike the traditional top-down reactive way of handling the disaster, the community-based approach to disaster management calls for a holistic bottom-up approach reposing its faith in local communities who are usually caught hapless in the epicenter of disasters. Despite the proven efficacy of community engagement in disaster management, it has few takers in the policy circuit. This study uses a qualitative approach with content analysis techniques. The present paper with special reference to the community involvement in disaster management in Indonesia and India, concludes that community engagement in addition to institutional cooperation is equally important for the successful mitigation of disaster.